An Empirical Study on the Relationship between China’s International Trade Development and Economic Growth - Hu Zheng, Serhii Tkachenko, Olena Potyshniak, Yevheniia Poliakova, Svitlana Prokhorchuk (International Journal of Advanced Science and Technology, 2020)
International trade is an important means for countries to communicate with each other and to make adjustments. It is also an important way for countries to increase their economic strength and increase the variety of products in the domestic market. Economic growth is an important indicator of the living standards of people in various countries, and it is a concrete manifestation of economic strength and comprehensive national strength. Whether a country’s international trade can promote the country’s economic growth, and how to promote economic growth, has been the issue of widespread concern. Since China’s reform and opening up, foreign trade has developed rapidly and this has also been accompanied by rapid economic growth. What is the relationship between China’s foreign trade and economic growth in this process? In order to answer this question, this paper uses the analytical methods of empirical research on the basis of economic theory research to select China’s economic development level from 2010 to 2019, Data such as import and export trade volume were analyzed empirically using econometric software STATA. Finally, it was concluded that China’s development of international trade has promoted economic growth. At the same time, this paper also puts forward some policy suggestions for effectively improving the development of foreign trade in light of the current situation of China’s foreign trade and economic growth, combined with empirical research results, to better promote the sound and rapid development of China’s economy.